The establishment responds: power, politics, and protest since 1945 - Fahlenbrach, Kathrin (Palgrave Macmillan transnational history series, 2012)
"Protest movements have been analyzed widely by several disciplines in recent decades,but the larger repercussions they caused in social institutions and international affairs have largely been neglected. This volume fills this gap by examining the many ways in which political parties, the business world, foreign policymakers, and the intelligence community experienced, confronted, and even actively contributed to domestic and transnational forms of dissent"--